Hartaita lauluja. 1 - Ahvenainen, Pauli; Holma, Juha; Kalaranta, Sirkka-Liisa; Kiiski, Paavo; Lindqvist, Antti; Salakka, Teppo; Tamminen, Jussi; Ödner, Maija (Mieskuoroliitto, 2002)
36 kappaletta.
Keywords: mieskuorot; manskörer